Sosialisasi Pengisian Kelengkapan Dokumen Rekam Medis Rawat Inap Pada Pasien Diabetes Mellitus Di Rsu Imelda Medan - Ali Sabela Hasibuan; Ratna Dewi; Hamonangan Damanik; Esraida Simanjuntak; Mei Sryendang Sitorus (Pusat Riset dan Inovasi Nasional, 2023)
This service aims to find out the number of incomplete medical records for inpatient diabetes mellitus patients at Imelda Hospital, Medan. This service uses a descriptive method, namely a research method carried out with the main aim of finding out the number of incomplete filling in inpatient medical records for Diabetes Mellitus patients. From the results of the service, it was found that the number of incomplete filling out of the integrated record form was found to be 17.40%, initial assessment was 15, 22% of medical resumes were 9.79% and informed consent was 17.40%, the doctor's name was 21.74% and the doctor's signature was 8.70%, while for patient identification, anesthesia records and the operation report is filled out completely. The suggestions from the author are: (1) the permanent procedure for analyzing incompleteness in filling out inpatient medical records needs to be revised so that all forms are analyzed, and continuous socialization needs to be carried out.